Introduksi Compulsory Education Dengan Metode Voorlicting Sebagai Upaya Pencegahan Bullying Di SDN 212 Harapan - Dini Dwi Rai Anggraeni; Salman Zakariya Dahlan; Indy Farida Putri; Dian Aulia Mareti; Maulia Depriya Kembara (Pusat Riset dan Inovasi Nasional, 2024)
The rise of bullying cases that occur in Indonesia and the many cases of children dropping out of school are the reasons researchers take the topic of the importance of compulsory education for children in Indonesia as a prevention of bullying. Using a qualitative method with an in-depth approach through interviews, observation and counseling conducted to 40 elementary school students in the Bandung area. In-depth interviews were conducted with students who experienced bullying and 2 teachers as guardians of students. Researchers get the results of children in the school already know the meaning of bullying but sadly there are still children who are victims of bullying, some victims get bullying because of physical limitations. After conducting counseling, there was a significant change, including students knowing the importance of avoiding bullying.